Analysis of albedo versus cloud fraction relationships in liquid water clouds using heuristic models and large eddy simulation. Issue 13 (12th July 2017) - Feingold, Graham; Balsells, Joseph; Glassmeier, Franziska; Yamaguchi, Takanobu; Kazil, Jan; McComiskey, Allison
Abstract: The relationship between the albedo of a cloudy scene A and cloud fraction f c is studied with the aid of heuristic models of stratocumulus and cumulus clouds. Existing work has shown that scene albedo increases monotonically with increasing cloud fraction but that the relationship varies from linear to superlinear. The reasons for these differences in functional dependence are traced to the relationship between cloud deepening and cloud widening. When clouds deepen with no significant increase in f c (e.g., in solid stratocumulus), the relationship between A and f c is linear. When clouds widen as they deepen, as in cumulus cloud fields, the relationship is superlinear. A simple heuristic model of a cumulus cloud field with a power law size distribution shows that the superlinear A ‐ f c behavior is traced out either through random variation in cloud size distribution parameters or as the cloud field oscillates between a relative abundance of small clouds (steep slopes on a log‐log plot) and a relative abundance of large clouds (flat slopes). Oscillations of this kind manifest in large eddy simulation of trade wind cumulus where the slope and intercept of the power law fit to the cloud size distribution are highly correlated. Further analysis of the large eddy model‐generated cloud fields suggests that cumulus clouds grow larger and deeper as their underlying plumes aggregate; this is followed by breakup of large plumes and a tendency to smaller clouds. The cloud and thermal size distributions oscillate back and forth approximately in unison. Key Points: We address the relationship between key cloud field macroscale properties: albedo and cloud fraction We present a new heuristic model for shallow cumulus size distribution and optical properties Large eddy and heuristic models both suggest oscillations in the power law cloud size distribution